Efektivitas Group Based Educational Program Terhadap Self Efficacy dan Kepatuhan Pengobatan pada Pasien Diabetes Mellitus: A Systematic Review - Nita Tri Septiana; Tintin Sukartini; Padoli Padoli (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Background: Group-Based Education Program (GBEP) is an intervention to improve self efficacy and treatment adherence in diabetes mellitus patients. Objective: To explain the effectiveness of group-based education programs on self-efficacy and treatment adherence in patients with diabetes mellitus. Methods: The database used in this studied was Scopus, Springerlink, and PubMed was limited to the last 5 years of publication from 2015 to 2019, full-text article and in English. The keywords used were "group-based education programs" AND "self efficacy" AND "treatment adherence" AND "diabetes mellitus”. This systematic review uses 12 articles according to the inclusion criteria. Results: GBEP has had effectiveness to increase self efficacy and treatment adherence by stimulating cognitive, perceptions, norms, beliefs and spiritual. Conclusion: GBEP has a significant effect in increasing self efficacy and treatment adherence in diabetes mellitus patients. Keywords: group based educational program; self efficacy; treatment adherence; diabetes mellitus ABSTRAK Latar belakang: Group Based Educational Program (GBEP) merupakan intervensi edukasi berbasis kelompok untuk meningkatkan self efficcy dan kepatuhan pengobatan pada pasien diabetes mellitus. Tujuan: Mengidentifikasi efektivitas group based educational program terhadap self efficacy dan kepatuhan pengobatan pada pasien diabetes mellitus. Metode: Database yang digunakan dalam studi ini adalah Scopus, Springerlink dan Pubmed terbatas publikasi 5 tahun terakhir dari 2015 hingga 2019, full text article, dan berbahasa Inggris. Kata kunci yang digunakan adalah “group based educational program” AND“self efficacy”AND “treatment adherence” AND “diabetes mellitus. Systematic review ini menggunakan 12 artikel yang sesuai dengan kriteria inklusi. Hasil: GBEP memiliki efektivitas pada self efficacy dan kepatuhan pengobatan dengan menstimulasi kognitif, persepsi, norma, kepercayaan, dan spiritual, sehingga meningkatkan keyakinan dan kemampuan menjalankan pengobatan sesuai rekomendasi. Kesimpulan: GBEP signifikan dapat meningkatan self efficacy dan kepatuhan pengobatan pasien diabetes mellitus. Kata kunci: group based educational program; self efficacy; treatment adherence; diabetes mellitus